Comparative Study of the Sorogan Method and Deliberation Method to Improve Kitab Kuning Reading Ability - Miftahuddin; Nuruddin, Muhammad (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2024)
This study was to determine how the comparison between the sorogan method and the method of deliberation on the ability to read the book on the students of Madrasah Ihya " Ulumiddin. This study the authors used quantitative methods. This study has three formulations of the problem, how the results of the Sorogan method in improving the ability to read The Kitab Kuning in Madrasah Ihya " Ulumiddin? How are the results and deliberations in improving the ability to read The Kitab Kuning in Madrasah Ihya " Ulumiddin? How the results of the comparison of Sorogan and Musyawaroh methods in improving the ability to read The Kitab Kuning in Madrasah Ihya " Ulumiddin PP Darussalam Lirboyo Kediri. The results, the ratio between the variables of sorogan and deliberation method to the variable ability to read the book (Y) is 0.764 or if it is projected to be 76.4%, and R calculate the variable sorogan method there is a comparison with the variable ability to read the book (Y) is 0.667 or if it is projected to be 66.7%. It can be concluded sorogan method is more effective on the ability to read the book.